Zero-Delay and Causal Single-User and Multi-User Lossy Source Coding with Decoder Side Information - Kaspi, Yonatan; Merhav, Neri (IEEE transactions on information theory, 2014)
We consider zero-delay, single-user, and multi-user source coding with an average distortion constraint and decoder side information. The zero-delay constraint translates into causal (sequential) encoder and decoder pairs as well as the use of instantaneous codes. For the single-user setting, we show that optimal performance is attained by time sharing at most two scalar encoder-decoder pairs, that use zero-error side information codes. Side information look-ahead is shown to be useless in this setting. Furthermore, we show that even without delay constraints, if either the encoder or decoder are restricted a priori to be scalar, the performance loss cannot be compensated by the other component, which can be scalar as well without further loss. Finally, we show that the multi-terminal source coding problem can be solved in the zero-delay regime and the rate-distortion region is provided.